Circulating adipokine levels and preeclampsia: A bidirectional Mendelian randomization study - Chen, Xiaoyan; Liu, Zhaoming; Cui, Jingen; Chen, Xiaolan; Xiong, Jing; Zhou, Wei (Frontiers in Genetics, 2022)
Background: Several observational studies have demonstrated that significantly rising circulating adipokine levels are pervasive in preeclampsia or eclampsia (PET) disorder. However, it remains unclear whether this relationship is causal. In this study, we sought to elucidate the causal effects of circulating adipokine levels on PET. Methods: Summary-level data and independent genetic variants strongly associated with common adipokine molecules (adiponectin, leptin, resistin, sOB-R, and PAI-1) levels were drawn from public genome-wide association studies (GWAS). Additionally, the corresponding effects between instrumental variables and PET outcome were acquired from the Finn-Gen consortium, including 4743 cases and 136325 controls of European ancestry. Subsequently, the inverse-variance weighted (IVW) approach was applied for the principal two-sample Mendelian randomization (MR) and multi-variable MR (MVMR) analyses. Various complementary sensitivity analyses were then carried out to determine the robustness of our models. Results: The results of IVW method did not reveal any causal relationship shared across genetically predisposed adipokine levels and PET risk (for adiponectin, OR=0.86, 95% CI: 0.65-1.13, P=0.274). Additionally, no significant associations were identified after taking into account five circulating adipokines in MVMR research. Complementary sensitivity analysis also supported no significant associations between them. In the reverse MR analysis, genetically predicted PET risk showed a suggestive association with elevating PAI-1 levels by IVW method (Beta=0.120, 95% CI: 0.014, 0.227, P=0.026). Furthermore, there were no strong correlations between genetic liability to PET and other adipokine levels (P>0.05). Conclusion: Our MR study did not provide robust evidence supporting the causal role of common circulating adipokine levels in PET, whereas genetically predicted PET may instrumentally affect PAI-1 levels. These findings suggest that PAI-1 may be a useful biomarker for monitoring diagnosis or therapy of PET rather than therapeutic target for PET.